Gender Differences in Performing Refusal Strategies to an Invitation by Students at SMAN 4 Padang. - Nadia Agustina; Hamzah Hamzah (Universitas Negeri Padang, 2023)
One of the most fundamental English skill is speaking. To practice all of those subjects correctly, the students not only have to understand the grammatical aspect but also the pragmatic aspect espescially for second language lerners. In this context the students not only focus on what is written but also what is happen, whom they talking to and what are they situation they face. The aimed of this research is to find out the refusal strategies used by gender to an invitation and what the differences between them. This research used descriptive study. Through random sampling, twenty male and female from the 12 grade of the students were selected. Data were collected through discourse completion test (DCT). The result showed that both gender is mostly using indirect strategy to refuse an invitation. However, male tend to give the shorter refusal and not pay attention to the context of the interlocutor, for example the power and social distance of the interlocutor. Beside, female students used more indirect and longer answer and strategy to refuse an invitation and make it clear by combined some refusal strategy, such as statement of regret, wish and statement of alternative.